The viability of fresh and extended semen of stallion with different sperm concentration in Dimitropoulos-modified extender - ., Yudi; Arifiantini, I; Purwantara, B; Yusuf, T.L (Indonesian Animal Sciences Society, 2008)
The objective of the experiment was to study the motility and viability of spermatozoa of fresh semen, and the quality of extended semen with different sperm concentration in Dimitropoulos-modified extender. Semen was collected using artificial vagina from three 4-8 year old stallions (different breed). Semen characteristics and quality was evaluated macro- and microscopically. For longevity evaluation, semen was stored at room and chilled temperature, and was evaluated for motility and viability every 3 h. Prior extension, semen was centrifugated at 3000 rpm for 20 minutes. The condensed sperm was re-suspended in Dimitropoulos (DV) supplemented with 50 mM fructose with the concentration of 200, 100 and 50 x 106 spz/mL. All samples were stored at room and chilled temperature, and was evaluated for motility and viability every 3 h and 12 h for room and chilled temperature. Results of the experiments indicated that fresh semen characteristics was fairly good. For longevity evaluation, semen with motility of 48.33 and 10.42% was observed at 3 h and 12 h after the onset of storage. The extended-semen with 50 x 106 spz/mL showed significantly higher in term of motility and viability (P<.05) than that with 200 x 106 spz/mL, but for that of 100 x 106 spz/mL. It is recommended that sperm concentration should be 50 x 106 spz/ml for a long period storage with reasonable good quality. Key words: Stallion, Semen, Sperm Concentration, Dimitropoulos